9n-3(2n-1)=18

Simple and best practice solution for 9n-3(2n-1)=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9n-3(2n-1)=18 equation:


Simplifying
9n + -3(2n + -1) = 18

Reorder the terms:
9n + -3(-1 + 2n) = 18
9n + (-1 * -3 + 2n * -3) = 18
9n + (3 + -6n) = 18

Reorder the terms:
3 + 9n + -6n = 18

Combine like terms: 9n + -6n = 3n
3 + 3n = 18

Solving
3 + 3n = 18

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 3n = 18 + -3

Combine like terms: 3 + -3 = 0
0 + 3n = 18 + -3
3n = 18 + -3

Combine like terms: 18 + -3 = 15
3n = 15

Divide each side by '3'.
n = 5

Simplifying
n = 5

See similar equations:

| 8(b-c)+2c-3b=0 | | 6y-1=2y+4 | | 2b+3=5b+15 | | -20-4.6x=-2.3x+16.8 | | -34-154= | | x^2+x-.4444444=0 | | -54=2x | | -(2n-1)+6(n+3)=-4-(7n-1) | | -1.278+t=-1.042 | | j+4= | | -8=n+4 | | x^2-23x+79=0 | | 2b+16a=1 | | 0=-y^2+28y+98 | | 0=y^2+28y+98 | | a^2+b^2=5 | | -3(4n+2)+2(n-6)=-2(n+1) | | 2y+7x=4x | | 9z+5=7x+6 | | 3(2x-6)+6(x-2)=3(3-5x)+5x-7 | | 4(x-2)-3(x-1)=2(x+6) | | (3x-4)(x^2-6x+6)= | | (x+5)(x+5)=25 | | (11+i)+(3-15i)= | | (x^2+15)(x+30)=3000000 | | 6x(x-1)=7-25x | | (x^2+15)(x+30)=300 | | x^2=5(x+280) | | (-4+3i)-(-1+6i)= | | (2x^3+12)(x^2-15)=117 | | (2x^3+12)(x^2-15)=333 | | -4c(3+5)=32 |

Equations solver categories